Peningkatan Prestasi Belajar Melalui Penerapan Model Pembelajaran Langsung Pada Pembelajaran Mesin Milling CNC - Bambang Suyanto (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2019)
The research purpose ofÂ  this study is improve student learning outcomes. To study the response of learners to apply direct instruction model (DI). To determine the activity of students during the learning process takes place. This study applied milling machine CNC majors of SMKN 1 Cirebon on the topic the program milling machine CNC. The object of this study was student class XII PM1 year 2016/2017which consists of 34 students. The kind of this research is Classroom Action Research which consists of several cycles refers to completeness criteria specified. When the cycle of first step is can not obtained a value corresponding to the criteria of completeness, the cycle will continue until the obtained results are in accordance with the criteria of completeness. Each cycle has stages, planning, action, observation and reflection. Data obtained from this study were collected and analyzed qualitative description, while the instruments used in this study include the observation sheet learner activity, achievement test sheets, questionnaires learners. The results of this study are the application of direct instruction model on topic charging system using the program milling machine CNC courses, learning outcomes increasing student mastery criteria for achieving a grade of 75 (B+). This is indicated by the increasing learning outcomes in the first cycle is only one study that reached mastery criteria but on the second cycle all learners have achieved the final learning criteria score â‰¥ 75 (B+) and the activity of the learner's mean score = 86,77 to 97,22 , despite of the fact that the response decreased firstly learners first cycle with an average percentage of 79,99 % decreased to 77,64 %.